Combinatorial treatments of tamoxifen and SM6Met, an extract from Cyclopia subternata Vogel, are superior to either treatment alone in MCF-7 cells - van Dyk, Lorinda; Verhoog, Nicolette J. D.; Louw, Ann (Frontiers in Pharmacology, 2022)
Synergistic drug combinations are not only popular in antibiotic, anti-microbial, immune disease (i.e., AIDS) and viral infection studies, but has also gained traction in the field of cancer research as a multi-targeted approach. It has the potential to lower the doses needed of standard of care (SOC) therapeutic agents, whilst maintaining an effective therapeutic level. Lower dosages could ameliorate the fundamental problems such as drug resistance and metastasis associated with current SOC therapies. In the current study, we show that the combination of SM6Met with (2)-4-hydroxytamoxifen (4-OH-Tam, the active metabolite of tamoxifen) produces a strong synergistic effect in terms of inhibiting MCF7 ER-positive (ER+) breast cancer cell proliferation and that a 20 times lower dose of 4-OH-Tam in combination with SM6Met is required to produce the same inhibitory effect on cell proliferation as 4-OH-Tam on its own. Cell cycle analyses of the best combination ratios of SM6Met and 4-OH-Tam also suggests that the combination results in increased accumulation of cells in the S-phase and in the apoptotic phase. Moreover, the best combination ratio (20:1) of SM6Met with 4-OH-Tam displayed greater anti-metastatic potential in terms of inhibiting ER+ breast cancer cell migration, invasion, and colony formation than the SOC therapy alone, suggesting that SM6Met together with 4-OH-Tam could be a viable drug combination for not only delaying resistance and ameliorating the negative side-effects associated with current SOC therapies, like tamoxifen, but could also provide a novel, more affordable therapeutic alternative for treating or preventing ER+ breast cancer metastasis.